Thermal Performance of a Branching-Channel Liquid Cooling System for Cylindrical Li-Ion 18650 Batteries - Anggie Topan Wijaya; James Julian; Fitri Wahyuni; Riki Purba; Fathin Madhudhu; Elvi Ermadani; Adi Winarta (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
Lithium-ion batteries need effective thermal management to avoid safety risks like thermal runaway. This study analyzes and optimizes a liquid cooling system. Battery Thermal Management System (BTMS) using a branching mini-channel cold plate design for eight Li-ion 18650 batteries. A Computational Fluid Dynamics model was developed to simulate performance at a 2C discharge rate with configurations of 3 (N3), 5 (N5), and 7 (N7) branches. The results, validated against experimental data, showed that all configurations kept maximum temperatures below 37°C and maintained temperature uniformity (ΔT) below 5°C. Increasing branches reduced pressure drop, with the N7 design showing the lowest ΔP of 5.16 Pa. Although it had a lower heat transfer coefficient, N7 achieved the highest J/F factor, indicating optimal thermo-hydraulic performance for liquid-cooled battery systems.